ANALISIS STABILITAS AGREGAT DAN SIFAT FISIK TANAH DENGAN PENAUNG BERBEDA PADA SISTEM AGROFORESTRI DI LAHAN KOPI SUMBERMANJING WETAN, KABUPATEN MALANG - Rensy Faradina Hikmawati; Sugeng Prijono (Jurnal Tanah dan Sumberdaya Lahan, 2022)
One of the damages that can occur in the soil structure is a decrease in aggregate stability. This study aimed to analyze the relationship between the stability of soil aggregates on a land by considering the level or type of land cover and the influence of several physical properties of the soil on coffee grounds. In this study there were four treatments with five replicates using a randomized block design at 2 depths, namely 0-20 cm deep and 20-40 cm deep. The treatments were based on different types of shade plants, namely P1 (cocoa shade), P2 (sengon shade), P3 (lantoro shade), and P4 (gamal shade). The results showed that lowest and highest soil aggregate stability values at the top depth (0-20 cm) were found in treatment P1 (cocoa shade) of 1.76 mm and P4 (gamal shade) of 3.33 mm. While at the depth of 20-40 cm, the highest and lowest values were found in the treatment P3 (lamtoro shade) of 1.92 mm and P1 (cocoa shade) of 2.37 mm. The stability of soil aggregates significantly affected soil bulk density, specific gravity, porosity, and organic matter. All treatments gave a significant effect on the thickness of the litter. The highest and lowest values were found in the treatment P4 (shade gamal) and P2 (shade sengon) of 3.4 cm and 1.7 cm, respectively.